Pengaruh Model Inkuiri Terbimbing terhadap Hasil Belajar IPAS Siswa Kelas IV SD Inpres 5 Taipa Laga - Salli, Mufida N; Fitriah Aras, Nurul; Zulnuraini, Zulnuraini; Rahmawati, Dyah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine whether there is an influence of the guided inquiry model on the learning outcomes of fourth-grade students of SD Inpres 5 Taipa Laga. The design of this study is a Quasi-experimental design using Two Group Pretest – Posttest designs. The population in this study is all fourth-grade students of SD Inpres 5 Taipa Laga, totaling 34 students. The sampling technique used in this study is a purposive sample with a sample size of 34 students from grades IVa and IVb consisting of 17 students in grade IVa as the experimental class and 17 students in grade IVb as the control class. Research data were collected through observation, test administration and documentation. Data were analyzed quantitatively through paired sample t-test. Based on the significant value of the Paired Sample T Test obtained is 0.000, with a significant value of T-test <0.05 (0.000 <0.05) and a significance level of 5% (0.05), then H1 is accepted and Ho is rejected. So it can be concluded that there is an influence of the guided inquiry model on the science learning outcomes of fourth-grade students of SD Inpres 5 Taipa Laga. The guided inquiry learning model makes students active in the learning process so that it is able to improve science learning outcomes.